2003
DOI: 10.1016/s1535-6108(03)00021-7
|View full text |Cite
|
Sign up to set email alerts
|

PTEN tumor suppressor regulates p53 protein levels and activity through phosphatase-dependent and -independent mechanisms

Abstract: We show in this study that PTEN regulates p53 protein levels and transcriptional activity through both phosphatase-dependent and -independent mechanisms. The onset of tumor development in p53(+/-);Pten(+/-) mice is similar to p53(-/-) animals, and p53 protein levels are dramatically reduced in Pten(-/-) cells and tissues. Reintroducing wild-type or phosphatase-dead PTEN mutants leads to a significant increase in p53 stability. PTEN also physically associates with endogenous p53. Finally, PTEN regulates the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
391
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(426 citation statements)
references
References 55 publications
23
391
0
12
Order By: Relevance
“…19,20 A functional p53 binding site has been identified within the PTEN promoter region, suggesting that p53 is able to regulate PTEN expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 A functional p53 binding site has been identified within the PTEN promoter region, suggesting that p53 is able to regulate PTEN expression.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Recently, important interactions between the PI3K-AKT and p53 signaling pathways have been described. [19][20][21] Studies on cell line suggest that activation of the PI3K pathway through PTEN or PIK3CA mutations causes activation of p53. It has been reported that activation of the PI3K-AKT pathway together with p53 inactivation results in malignant transformation.…”
mentioning
confidence: 99%
“…Given the ability of PTEN to indirectly stabilize p53 protein through antagonizing the Akt-MDM2 pathway (4,10,26) or by directly increasing p53 acetylation (27), decreased p53 activity in PTEN-deficient tumor cells should be expected and would explain the comparably preferential activity of caffeine in radiosensitizing p53-deficient (Table 1A; refs. 23,24) and PTEN-deficient tumor cells (Table 1A; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas p53 enhances PTEN transcription, PTEN physically stabilizes the p53 protein by direct interaction, in addition to transcriptional downregulation of MDM2 through the P1 promoter and inhibition of Akt-dependent MDM2 phosphorylations. 93,[169][170][171][172][173] DNA damage, on the other hand, may lead to p53-dependent degradation of Akt. 174 Although somatic mutations in PTEN occurs at high frequency in some cancers, like endometrial carcinomas, they are rare in breast cancer.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%